COLLECTIVE MEMORY, IDENTITY AND THE LEGACIES OF SLAVERY AND INDENTURE ([S.l.])
1 online resource
Keywords: The Caribbean history provides a rich study of the different forms of labour systems that have historically marked the politics of the coloniser and the colonised. It further provides the basis for an essential study for discourses on colonialism and capitalism. This interdisciplinary volume bridges the gap between historiography and the present-day diasporic communities, which emerged from the slave trade and indenture. Through case studies from the Caribbean context, the volume demonstrates how the region's historical labour mobility remains central to performances and negotiations of collective memory and identity. Please note: Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh and Sri Lanka.